Measuring business schools' service quality in an emerging market using an extended SERVQUAL instrument - E. R. Mbise; R. S.J. Tuninga (South African Journal of Business Management, 2016)
An extended SERVQUAL instrument is developed, validated and used to measure perceived service quality delivered to students by business schools in an emerging market economy. A longitudinal survey is conducted with selected students in their final year of study from two business schools in an emerging market economy. The use of the extended SERVQUAL model is suggested to monitor student/employee expectations and perceptions during and after the education service delivery process. Students attach different weights to the service quality dimensions. A new Process Outcome dimension is found to substantially add to the SERVQUAL model and is more important than the other dimensions. The validity of the extended SERVQUAL model for practical use is α 0.95. Prediction of the level of service quality delivered, using four dimensions, indicates that the level of service quality is explained mostly by Process Outcome and Tangibles dimensions. It is suggested that using the extended SERVQUAL model as a tool can enable managers of business schools to identify the factors on which students/employees base their quality assessment of the education services they receive. Knowledge of these factors will enable managers in emerging economies to periodically assess, sustain and improve quality of the whole service delivery process. Priorities can be set to allocate scarce resources properly to make effective investment decisions to improve quality per school and in higher education, in general. The paper further suggests that regulatory bodies make use of this model when comparing performance of business schools, focusing on student experiences as a supplement to the traditional performance measures.
Keywords: 650